1979
DOI: 10.1002/cne.901830406
|View full text |Cite
|
Sign up to set email alerts
|

Efferent projections from temperature sensitive recording loci within the marginal zone of the nucleus caudalis of the spinal trigeminal complex in the cat

Abstract: The efferent projections from nucleus caudalis of the spinal trigeminal complex in cats were studied with retrograde and anterograde axonal transport techniques combined with localization of recording sites in the thalamus and marginal zone of nucleus caudalis to innocuous skin cooling. Results showed brainstem projections from nucleus caudalis to rostral levels of the spinal trigeminal complex, to the ventral division of the principal trigeminal nucleus, the parabrachial nucleus, cranial motor nuclei 7 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(24 citation statements)
references
References 84 publications
3
21
0
Order By: Relevance
“…Cells dorsal to Int5 appear to lie in Su5. Many previous studies have shown that Sp5O, Sp5I, and Sp5C give rise to axons which reach the spinal cord (Kuypers and Maisky 1975;Craig 1978;Burton et al 1979;Matsushita et al 1981;Ruggiero et al 1981;Leong et al 1984;Gross and Oppenheim 1985;Phelan and Falls 1991;Masino and Knudsen 1992;Diagne et al 2006). Our results are consistent with these studies.…”
Section: The Nucleus Of Solitary Tractsupporting
confidence: 83%
“…Cells dorsal to Int5 appear to lie in Su5. Many previous studies have shown that Sp5O, Sp5I, and Sp5C give rise to axons which reach the spinal cord (Kuypers and Maisky 1975;Craig 1978;Burton et al 1979;Matsushita et al 1981;Ruggiero et al 1981;Leong et al 1984;Gross and Oppenheim 1985;Phelan and Falls 1991;Masino and Knudsen 1992;Diagne et al 2006). Our results are consistent with these studies.…”
Section: The Nucleus Of Solitary Tractsupporting
confidence: 83%
“…In both cases, terminal labeling is located bilaterally in the brainstem at several sites that are consistent with prior examinations of the projections of lamina I cells (Burton et al, 1979;Craig, 1995;Westlund and Craig, 1996), i.e., in the nucleus of the solitary tract (A2 region), the caudal and rostral ventrolateral medulla (A1 and C1 regions), and the ventrolateral (A5) and dorsolateral (A7) regions of the caudal pons. In the case with the large injection, there is bilateral labeling in the medial parabrachial nucleus; but in the case with PHA-L injections nearly restricted to the SP-free subregion of lamina I, there is no labeling in the parabrachial nucleus.…”
Section: Anterograde Tracer Injectionssupporting
confidence: 63%
“…Its role in nociception is still unclear, although it has been suggested that it is involved in the affective or motivational components of pain (see AlbeFessard et al 1985 andJones 1985 for reviews) as well as in the modulation of other nociceptive pathways (Olausson 1989). Projections to ILC from the trigeminal subnucleus caudalis have been described in the rat (Carstens et al 1988), cat (Stewart and King 1963;Berkley 1980) and primate (Tiwari and King 1974;Ganchrow 1978) although other studies in the cat (Burton et al 1979;Shigenaga et al 1983) could not confirm this. The receptive fields of nociceptive neurones in the ILC have been shown to be large, contralateral or bilateral (Dong et al 1978), and to involve the face (Dong et al 1978;Yokota et al 1985;Yokota 1988).…”
Section: Discussionmentioning
confidence: 87%